Effect of losartan and atenolol on insulin sensitivity in nondiabetic hypertensive patients - Bharati, Sandesh Madhukar (J Pharmacol Pharmacother, 2016)
OBJECTIVE: To study the effects of losartan and atenolol on glucometabolic parameters in nondiabetic hypertensive patients. MATERIALS AND METHODS: In a prospective, open-label, parallel group study, nondiabetic patients with mild to moderate hypertension were randomized to either losartan (titrated from 50 to 100 mg/day, n = 20) or atenolol (titrated from 25 mg to 100 mg/day, n = 20) for period of 24 weeks. At baseline, 12 and 24 weeks fasting plasma glucose (FPG), fasting plasma insulin (FPI), homeostasis model assessment for insulin resistance (HOMA-IR) apart from lipid parameters, mean systolic, and diastolic blood pressures levels were determined. RESULTS: At the end of study, losartan significantly (P < 0.05) reduced FPG, FPI, and HOMA-IR compared to atenolol and baseline. While atenolol increased the HOMA-IR levels significantly compared to the baseline. CONCLUSIONS: Losartan improved the insulin sensitivity while atenolol worsened it. Losartan is better than atenolol for its effects on the glucose-insulin metabolism.